NILAI-NILAI SOSIAL DALAM NASKAH DRAMA SEPASANG MERPATI TUA KARYA BAKDI SOEMANTO - Amrullah, Dea (Universitas Tanjungpura, 2024)
This research aims to describe the social values contained in the drama script A Pair of Old Pigeons by Bakdi Soemanto. The research uses descriptive methods in the form of qualitative research. This research data is the form of words, phrases, and sentences that contain social values contained in drama text. The results of this research are as follows. Social values related to the value of compassion include love and affection, loyalty, mutual assistance, kinship, and concern. Social values related to the value of responsibility include a sense of belonging, obligation, and discipline. Social values related to the value of harmony in life include justice, tolerance, and cooperation.